Germinoma with Involvement of Midline and Off-Midline Intracranial Structures - Monica Graciela Loto; Karina Danilowicz; Santiago González Abbati; Rafael Torino; Alejandro Misiunas (Case Reports in Endocrinology)
Germinomas are malignant intracranial germ tumors, usually found in suprasellar regions. Less than 10% are localized in off-middle structures, and synchronous involvement of both structures has only exceptionally been published. A case of an 18-year-old male patient with progressive right-sided hemiparesis and panhypopituitarism was reviewed. Brain MRI showed a solid mass involving pituitary and hypothalamus with thickening of pituitary stalk, high intensity lesions on T2-weighted imaging in left internal capsule, caudate nucleus, globus pallidus, and mild atrophy of the left internal capsule and cerebral peduncle. Nonadenomatous lesions were considered in the differential diagnosis. Alfa-fetoprotein (AFP) levels were negative in both serum and cerebrospinal fluid (CSF), while β-human chorionic gonadotrophin (β-HCG) levels were slightly increased in CSF. A transsphenoidal biopsy identified a germinoma. Four cycles of chemotherapy with bleomicine, etoposide, and cysplatin were given, followed by radiotherapy, but patients died due to a recidiva. Conclusion. Germinoma must be considered in patients with insipidus diabetes with a sellar mass with thickening of pituitary stalk; and ectopic germinoma must be suspected in patients with slowly progressive hemiparesis with cerebral hemiatrophy. Even with a rare condition, colocalization of midline and off-midline germinoma must be suspected in the presence of these typical signs of both localizations.